Poetic Interpretation of the Qur’an: A Critical Study of Tafsir Al-Mubarok by Taufiqul Hakim - Akbar, Jamaluddin; Abdul Hakim (Journal of Ushuluddin and Islamic Thought, 2024)
The tradition of writing Islamic works in the form of naẓm has become an integral part of Islamic scholarship, particularly in Islamic boarding schools in Indonesia. However, the number of Qur’anic exegesis works composed in the form of naẓm is still limited. This artcle critically examines the poetic-based interpretation in Tafsir al-Mubarok by Taufiqul Hakim and its contribution to the development of exegesis in the archipelago. This study uses a qualitative approach with textual analysis that combines ‘arūḍ theory and stylistics. Data was obtained from a study of primary manuscripts supported by secondary literature related to tafsīr , pesantren traditions, and linguistic studies. The results of the study show that the application of naẓm in Tafsir al-Mubarok reflects the structured use of ‘arūḍ theory, particularly in the selection of baḥr rajaz , which is an important element in the pesantren tradition. The application of ‘arūḍ rules not only maintains the beauty of the language but also ensures the effective and poetic delivery of the exegesis message. Taufiqul Hakim’s significant contribution lies in integrating pesantren tradition with a modern approach through the use of three languages (Arabic, Javanese, and Indonesian), the hanging translation ( makna gandul ), the pegon script, and a systematic latin writing system. He not only preserves the traditional form of tafsir but also recontextualizes the method of interpretation to remain relevant in contemporary academic dynamics. Thus, Tafsir al-Mubarok serves as an educational tool in pesantren environments and contributes to the development of Qur’anic exegesis in the Nusantara region.